Black Dot Type Capitis Tinea Appreciates Bacterial Foliculitis - Radema Maradong Ayu Pranata; Rusmawardiana; Fifa Argentina (Jurnal RSMH Palembang, 2020)
Tinea capitis is a superficial fungal infection of the scalp and hair, which is seenpredominantly in children. In adults, it is usually related to immunocompromisedpatients and have an atypical features. In patients with end stage renal disease (ESRD),uremia is associated with immune suppression due to the impact of uremic milieu. Allspecimens of tinea capitis should be examined for microscopy, wood’s lamp andculture. Reported a case of 50–year-old male, animal husbandry, presented with itchypapules, pustules, patch alopecia and a hair loss for 6 months. Dermatologic featuresshowed papules, pustules, patch alopecia and black dot. The patient treated withketoconazole shampoo for 3 weeks without any improvement. He had an ESRD for 2years. Gram stain examination and culture showed no bacteri. Wood’s lampexamination showed no fluorescent. Potassium hydroxide (KOH) 10% from scalpscrapings and KOH 20% from hair showed a fungal elements, which support diagnosisof black dot tinea capitis. The patient treated with griseofulvin tablet 500 mg twice aday for 8 weeks, cetirizine tablet 10 mg once daily and 3x/week of ketoconazoleshampoo 2% showed improvement in clinical features and microscopic evaluation.